PERANCANGAN CHATBOT MENGGUNAKAN METODE FORWARD CHAINING SEBAGAI MEDIA PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING - Rafif Muhammad Irdian, Rafif (2020)
In learning a language chatbot can be used as a means of language learning aids so that users can practice their language skills. In designing a chatbot needed the right method to be able to work in accordance with the desired function. If chatbots are designed with the wrong method, chatbots cannot help someone in learning the language. Therefore, the author wants to create a chatbot learning media that can help preserve Indonesian by using the Forward Chaining method. The system will provide material and quizzes about the Indonesian language according to the material that the user wants. The expected outcome is that the system can assist in learning Indonesian for foreign speakers.